2023
DOI: 10.1002/adfm.202300113
|View full text |Cite
|
Sign up to set email alerts
|

Tetrabutylammonium Bromide Functionalized Ti3C2Tx MXene as Versatile Cathode Buffer Layer for Efficient and Stable Inverted Perovskite Solar Cells

Abstract: 2D Ti 3 C 2 T x MXene, possessing facile preparation, high electrical conductivity, flexibility, and solution processability, shows good application potential for enhancing device performance of perovskite solar cells (PVSCs). In this study, tetrabutylammonium bromide functionalized Ti 3 C 2 T x (TBAB-Ti 3 C 2 T x ) is developed as cathode buffer layer (CBL) to regulate the PCBM/Ag cathode interfacial property for the first time. By virtue of the charge transfer from TBAB to Ti 3 C 2 T x demonstrated by electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The PFOPy CIL shows remarkable PL peaks at 400 and 420 nm, while the PL signals are totally absent for the PFOPy-N CIL, indicating the efficient electron transfer between PFOPy and PDINN. Electron paramagnetic resonance (EPR) was further used to investigate electron transfer characteristics of interfacial materials, 37 and Fig. 3b displays the EPR results of PFOPy, PDINN and PFOPy-N in a solid state.…”
Section: Resultsmentioning
confidence: 99%
“…The PFOPy CIL shows remarkable PL peaks at 400 and 420 nm, while the PL signals are totally absent for the PFOPy-N CIL, indicating the efficient electron transfer between PFOPy and PDINN. Electron paramagnetic resonance (EPR) was further used to investigate electron transfer characteristics of interfacial materials, 37 and Fig. 3b displays the EPR results of PFOPy, PDINN and PFOPy-N in a solid state.…”
Section: Resultsmentioning
confidence: 99%
“…The latter method has raw materials which are less expensive than Ti 2 AlC and TiC precursors . Ti 3 AlC 2 is generally preferred as the precursor for the synthesis of MXene because it is stable at temperatures required for the synthesis process (1350 Ā°C or higher) . However, a less dense block of the Ti 3 AlC 2 MAX phase is easier to mill into powder without applying pressure.…”
Section: Synthesis and Processing Of Ti3c2t X Mxenementioning
confidence: 99%
“…Several review articles discussed the material properties of MXenes and their applications, especially in photocatalysis , and energy storage. āˆ’ The use of MXenes in general for optoelectronic applications was also summarized by Wang et al, Liu et al . and Hantanasirisakul et al Later on, numerous interesting developments were reported. āˆ’ Figure shows the timeline and major milestones of Ti 3 C 2 T x MXene over the years in the field of optoelectronic applications. Thus, an article solely focusing on the Ti 3 C 2 T x MXene and its optoelectronic applications would be appropriate now for researchers on this topic to stay up to date on the recent developments.…”
Section: Introductionmentioning
confidence: 99%
“…[66][67][68][69][70] To replace BCP, multiple EIMs such as organic small molecules, polymers, organic-inorganic hybrid compounds, and inorganic metal oxides have been developed and shown enhancement in both the efficiency and the stability for PSCs. [71][72][73][74][75][76][77] Organicinorganic hybrid EIMs with the advantages of both the structure tunability of organic molecules and the stability of inorganic materials have the potential to overcome the instability of the cathode interface. (TOASiW 12 ) (Fig.…”
Section: Cathode Interface Modification In P-i-n Pscsmentioning
confidence: 99%